Speech Delay Problem on Early Childhood Children in Paser Regency: A Neurolinguistics Analysis - Moch. Atim (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze speech delay phenomena among early childhood children in Paser Regency through a neurolinguistic perspective, focusing on the interaction between neural mechanisms, linguistic performance, and environmental influences. This study employed a qualitative case study design grounded in a neurolinguistic framework. Data were collected through in-depth interviews, participant observation, and document analysis involving children aged 3–6 years, their parents, and teachers. The data were analyzed using thematic and interpretative techniques, integrating linguistic domains (phonological, lexical, syntactic, and pragmatic) with neurolinguistic theory. The findings revealed that speech delay manifests as a multidimensional condition characterized by disruptions across phonological (articulation and phoneme substitution), lexical (limited vocabulary and retrieval difficulties), syntactic (telegraphic speech and grammatical omission), and pragmatic (impaired interaction and communication) domains. These linguistic deficits are closely associated with neurocognitive limitations, particularly in language-related brain regions and processing systems. Additionally, environmental factors—such as limited language input, low parental engagement, and excessive passive media exposure—significantly exacerbate the condition. The study also identifies challenges in early English language exposure, which may create cognitive overload when first language development is incomplete. In conclusion, speech delay should be understood as the result of dynamic interactions between neurolinguistic and environmental factors. Effective intervention requires an integrative approach combining early diagnosis, enriched linguistic input, and adaptive educational strategies. The study contributes to both theoretical development in neurolinguistics and practical implications for inclusive English language education.